Features of systemic autoimmune disease associated with anti-Ku antibodies (descriptions of two clinical cases) - Anna V. Torgashina; Anna N. Khelkovskaya-Sergeeva; Askat O. Abdykerimov; Alsu R. Khalmetova (Научно-практическая ревматология, 2024)
Anti-Ku antibodies are a special type of myositis-associated antibodies that are characteristic of patients with the overlap syndrome of systemic scleroderma and immune-inflammatory myopathy, as well as occurring in other autoimmune diseases. Patients with these antibodies have their own clinical and laboratory features of the disease and can be identified as a separate anti-Ku syndrome.For the first time in the domestic literature, descriptions of two clinical cases of the development of a cross syndrome associated with anti-Ku antibodies are presented. The features of the course of the disease and the response to various options for immunosuppressive therapy were analyzed.